ANALISIS PERKEMBANGAN REGULASI DAN STANDAR DI AKUNTANSI SEKTOR PUBLIK - Siregar, Ayu Lestari (CV. Pusdikra Mitra Jaya, 2025)
In today's era of openness, information plays a crucial role. It is an effective means of communication between members of the public, or between a particular entity and the surrounding community. In such circumstances, the presentation of comprehensive information will create transparency and, in turn, realize public accountability. This research uses the library research method, often referred to as the library research method. This approach relies on and analyzes existing literature. This involves searching, selecting, evaluating, and interpreting written sources relevant to the research topic being studied. The stages of drafting public regulations include identifying problems, discussing solutions, drafting regulations, discussing them, and establishing regulations. This is crucial to ensure that the resulting regulations are relevant and effective in addressing existing issues. Research by Neni Machfira and Tesa Sanjaya demonstrates the importance of analyzing public sector financial reports and the influence of financial regulations on budget absorption. Research by Rahmadhani highlights the need to implement public accounting standards to ensure compliance with existing regulations. Therefore, the development of regulations and standards in the public sector is crucial to achieve good governance, transparency and accountability necessary for the benefit of society and the overall development of the country.